Pelatihan Penulisan Artikel Ilmiah bagi Mahasiswa PGSD Universitas Nahdlatul Ulama Lampung - Lestari, Siti; Astuti, Dwilita; Setyawati, Astri; Supatmi, Ruri; Syafi’I, Arif; Oktaviani, Ulfa Tri (Pakis Journal Institute, 2026)
This training aims to improve students' scientific writing skills with a total of 35 participants in the Elementary School Teacher Education program at Nahdlatul Ulama University, Lampung. This training is structured in three stages: planning, implementation, and evaluation. The planning stage includes analyzing student needs, selecting appropriate training methods, and preparing the necessary materials. The implementation stage is learning to write scientific papers by students by attending training sessions, creating their own papers, and presenting the results. The evaluation stage shows that students understand, comprehend, and can manage the articles they have created well. Meanwhile, some students still experience difficulties in managing the class accounts they have created. The conclusion in the scientific writing training for students can be applied. Students acquire scientific article writing skills, which is a crucial step towards publication in reputable journals. Students develop a better understanding of the importance of writing and are enthusiastic about this training.